Nanoprobiotics: when technology meets gut health - Machado, Daniela (2020)
Nanotechnology is a fast-rising industry not defined by a single field of research, but as the convergence of disciplines, such as chemistry, biology, physics, mathematics, and engineering, which exploits the benefits of nanoscale dimensions and characteristics for application in the macroworld. Current applications vary widely from nanorobotic industry to simple household items. However, the combination of such phenomena with probiotic science, another emerging and potentially promising area for the prevention and treatment of several human gastrointestinal and extraintestinal disorders using beneficial microorganisms, gives birth to “nanoprobiotics,” a field that focuses on the application of nanoscience into the probiotic-related world. In this chapter, we will navigate through the basic nanotech and probiotic knowledge and the current technologies employed with success for probiotic delivery and, ultimately, discuss what possibilities lie ahead in the nanoprobiotic future.